On an inequality for concentration functions - Petrov, V. V. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. В. Петров. Об одном неравенстве для функций концентрацииV. Petrov. Vienos nelygybės koncentracijos funkcijoms